RUSLE factor C evaluation for the vegetation cover management in erosion control in the Birrís river basin, Costa Rica - Lianes, Elena (2009)
This work contributes to increase the knowledge about the relations between vegetation cover and water erosion. Land-use capability was determined according to MAG and MIRENEM and RUSLE C factor. The land-use capability of the plots consists of Classes V and VI, representing slopes of a 21% and 79%, respectively, slope being a main limitation. Only 21% of the plots showed an appropriate land use, which corresponds with forest, cutting pastures and pasture under a normal level of grazing. The calculated C factor, as expected, varies considerably between agricultural covers C=(0.3-0.4), and other vegetation covers C=(0.002 0.04). Agricultural C factors have lower values than those used in previous studies in the same basin; which seems to indicate that some of the overestimation of agricultural soil loss rates from previous studies has been corrected. To correct the land use conflict and decrease erosion, the implementation of integrated management practices for soil and water conservation is recommended, taking into account the vegetation cover proposals that better protect the soil, on the basis of the results of the present work.